Papa’s Baby, Mama’s Maybe: Reading the Black Paternal Palimpsest and White Maternal Present Absence in Nella Larsen’s Quicksand - Yolanda M. Manora (European Journal of American Studies)
In his 2006 award winning monograph In Search of Nella Larsen: A Biography of the Color Line, George Hutchinson shed new light not only on the biographical facts of Nella Larsen’s life as a biracial individual coming of age during an “era when ‘race’ trumped” all relationships, even those of family, but also on the effects these experiences had on her psychologically, especially on her ability to forge a relational life. Given her socially and psychically untenable subject position as the “too dark to pass” child in a white family and the sense of isolation and, ultimately, abandonment, that attended it, it’s little wonder that Larsen’s autobiographically-informed fictional narratives can be read as sites of relational failure. In this article, I locate the narrative absences at the center of Larsen’s first novel, Quicksand, and examine the manner in which they source the relational failures that render the protagonist, Helga Crane, incapable of fulfilling her promise as, in Deborah McDowell’s words, a “daring and unconventional heroine” (xi). Not only does the palimpsestic presence of the black paternal impede Helga’s quest for social legitimacy and place, the present absence of the white maternal, arguably a more critical lacuna, serves as the experiential and psychological source of Helga’s fundamental “lack somewhere”: her failure to develop a relational subjectivity.